Correlation Between Sepsis Bundle Compliance with Incidence of Acute Kidney Injury and Mortality in Sepsis Adult Patients - Eka Prasetiyawan; Arie Utariani; Edward Kusuma (Humanistic Network for Science and Technology (HNST), 2020)
Sepsis is serious medical condition with mortality rate around 25%. Sepsis cause multiorgan failure, including AKI (Acute Kidney Injury). One-hour sepsis bundle compliance is expected to prevent AKI and reduce patient mortality. Aims: Analyze the correlation between sepsis bundle compliance with incidence and progression of AKI and mortality in first 48 hours of treatment in the Resuscitation Room (Intensive) of RSUD Dr. Soetomo Surabaya. Methods: Observational retrospective study. Total sampling from medical record of adult sepsis patients who treated in Resuscitation/ Intensive Room of RSUD Dr. Soetomo in January - July 2019. Sepsis bundle compliance was assessed in first 1-hour patient was treated, then observed in first 48 hours of treatment, whether there was death or AKI. Results: Most of the 1-hour survival bundle sepsis compliance were classified as poor (51.6%) and very poor (26.9%). The highest component was antibiotic administration management (63.4%) and the lowest was fluid resuscitation (8.6%). There is significant correlation between sepsis bundle compliance with AKI incidence in the first 6 hours, p value= 0.048; contingency coefficient 0.280. Cumulatively, there is significant correlation between sepsis bundle compliance with mortality rates sepsis patients under 48 hours, p value: 0.000; contingency coefficient 0.614. There is significant correlation between bundle sepsis compliance to mortality under 6; 12; 42; and 48 hours. Conclusions: There is significant correlation between sepsis bundles compliance with AKI incidence in first 6 hours. There is significant correlation between sepsis bundle compliance to the mortality rate of sepsis patients under 48 hours of treatment. Keywords: compliance; one-hour sepsis bundle; AKI; mortality